Closed loop neurostimulation for epilepsy. Issue 3 (March 2016) - Carrette, S.; Boon, P.; Sprengers, M.; Vonck, K.; Raedt, R.
Abstract : Various neurostimulation modalities have emerged in the field of epilepsy. Despite the fact that delivery of an electrical current to the hyperexcitable epileptic brain might, at first, seem contradictory, neurostimulation has become an established therapeutic option with a promising efficacy and adverse effects profile. In "responsive" neurostimulation the strategy is to interfere as early as possible with the accumulation of seizure activity to prematurely abort or prevent an upcoming seizure. The design of technology required for responsive stimulation is more challenging compared to devices for open-loop neurostimulation. The achievement of therapeutic success is dependent on adequate sensing and stimulation algorithms and a fast coupling between both. The benefits of delivering current only at the time of an approaching seizure merit further investigation. Current experience with responsive neurostimulation in epilepsy is still limited, but seems promising.